Analisis Posisi Landasan Kebijakan Pendidikan Islam terhadap Standar Pendidikan Nasional - Fardana, Sefi Fifit; Rasyid, Muhammad Wafiq; Jayanti, Isna Maulida (MASALIQ, 2023)
Education is the main pillar of the establishment of a nation, education is an effort to design the future of humans as a generation that advances a nation. The national education system has set educational standards that are adopted in the implementation of Islamic education in Indonesia as a whole. This preference of course raises the question, to what extent the educational foundation has been met by national education standards. This descriptive-analytic study describes the foundation of Islamic education which is included in the national education standards. From this study it can be identified that the basis of Islamic education is relevant to the educational standards set by the national education system.